Dynamics of Czech Capital Flows : Capital Flows at Risk Approach - Wałoszková, Adriana; Witzany, Jiří, 1966-; Siuda, Vojtěch; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This thesis applies the Capital Flow at Risk (CFaR) framework to examine how global and domestic drivers affect non-resident debt capital flows in the Czech Republic. By integrating quantile regression with a skewed t-distribution fit, the approach captures distributional asymmetries and tail risks, which are often overlooked by mean-focused models. Empirical results reveal that external push factors, such as European risk aversion and the European Central Bank’s monetary policy stance, disproportionately influence the lower and upper quantiles of capital flows, indicating that sudden, volatile shifts in global markets can amplify both severe outflows and large inflows. Meanwhile, domestic pull factors, particularly GDP growth and the term spread, underscore the role of strong local fundamentals in attracting and sustaining capital inflows. Scenario analyses further demonstrate how exogenous shocks can shift both the position and shape of the distribution of future capital flows, highlighting that a quantile-based CFaR framework can serve as a critical tool for policymakers aiming to identify vulnerabilities, track evolving risks and employ appropriate policy response.
Vedoucí práce: Jiří Witzany
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses